The Impact of Decreased Individual Behavior and Organization Culture on Employee Performance in PT. Saran Bhuana Jaya - Yulia, Rasty; Herawati, Heny; Chandra, Dharnita (The International Journal of Education Management and Sociology, 2023)
The main problem in the following research is that the implementation of employee performance at PT. Sarana Bhuana Jaya is classified as inadequate. The purpose of this research is to evaluate how employees behave and the importance of habits that exist on the results of employee performance at PT. Sarana Bhuana Jaya. Based on this problem, the problem is classified into a number of sub-problems, namely 1). Does organizational culture and individual behavior have an impact on employee performance at PT. Bhuana Jaya Facilities. 2). Which variable has the most impact on employee performance at PT. Bhuana Jaya Facilities. This type of research includes quantitative research using an associative research approach whose purpose is to test the correlation of 2 or more variables. The data collection methods used were questionnaires, reference searches, documentation, and observations to determine the actual facts to support the results. Multiple regression analysis using the SPSS Version 22 program was used to describe the effects of a number of independent variables (X) on the dependent variable (Y). The results explain that individual behavior has a significant and positive impact on employee performance and organizational culture has a significant and positive impact on employee performance. And It turns out that individual behavior has an impact but not significant on employee performance while organizational culture variables have a significant impact on employee performance. Implications for the theory and practice are discussed.